2011
DOI: 10.1144/0016-76492010-042
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and extinction patterns in Permian floras from North China as indicators for environmental and climate change

Abstract: Permian continental sequences from North China contain previously unrecognized episodes of plant radiation and elevated extinction. The earliest extinction, in the Lower Shihhotse Formation (Roadian, Guadalupian), records a 45% floral species loss and is tentatively correlated with global extinctions amongst dinocephalian reptiles. Two younger extinctions are dated by correlating the Illawara Reversal and palaeomagnetic polarity sequences from Shanxi Province against global palaeomagnetic history. Missing data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 55 publications
4
54
3
Order By: Relevance
“…[7,11,13,[38][39][40]). The new age of approximately 260 Ma for the top of the Tapinocephalus AZ in South Africa is consistent with a further temporal link between Emeishan volcanism and tetrapod extinctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,11,13,[38][39][40]). The new age of approximately 260 Ma for the top of the Tapinocephalus AZ in South Africa is consistent with a further temporal link between Emeishan volcanism and tetrapod extinctions.…”
Section: Discussionmentioning
confidence: 99%
“…In the terrestrial realm, at least one extinction event among plant species has been identified in the Capitanian Upper Shihhotse Formation of Northern China, suggesting the loss of at least 56% of plant species within this stage [13]. Unfortunately, the age estimates for this sequence rely on palaeomagnetism and missing data within the stratigraphic profile has led to high uncertainty in their correlation with the marine timescale.…”
Section: Introductionmentioning
confidence: 99%
“…In the middle Permian there were also some local volcanic eruptions in north China (Zhao et al, 2010). The collision of the North China block with Siberia during the Permian and the Sino-Mongolian seaway closing during the middle Permian resulted in abundant volcanism along the northern margin of north China during this period (Zhao et al, 2010;Stevens et al, 2011). Therefore, these middle Permian eruptions in north China could also have ignited wildfires.…”
Section: Volcanic Eruption Eventsmentioning
confidence: 99%
“…The pollutant discharge and the concomitant temperature increase might have affected floral growth thereafter. According to Stevens et al (2011), three floral extinction events in north China in the lower Shihhotse Formation (upper-middle Permian Period), which directly overlies the Shanxi Formation, have been found. Therefore, we may deduce that enormous amount of harmful gases released and increased local temperatures could be one of the reasons for the floral extinctions that occurred after the time of the Shanxi Formation.…”
Section: Pollutant Release From Wildfiresmentioning
confidence: 99%
See 1 more Smart Citation